Management culture in Romania: Patterns of change and resistance - Kevin Dalton; Liz Kennedy (Journal for East European Management Studies, 2007)
This study examines how far restructuring has involved a change in leadership style and the development of new philosophies and approaches which derive from the Anglo-American model of 'people management'. During the Communist period, Romania experienced a highly centralised system of management. Broader currents of historical and political culture also served to inculcate values of bureaucratic formalism. In transitional times it appears that the management role is being re-defined and management culture is changing. This article seeks to understand these changes in the culture and identity of Romanian management by examining experience in a range of organisations. It also considers how far Anglo-American values of HRM and managing are relevant to a country where the wider cultural and historical experience differs so strikingly from that in the West. – – Diese Studie überprüft, wie sehr die Restrukturierung den Führungsstil und die Entwicklung von neuen Philosophien und Ansätzen, die vom angloamerikanischen Modell des 'People Management' abgeleitet sind, beeinflußte. Während der Kommunistischen Periode besaß Rumänien ein stark zentralisiertes Managementsystem. Historische und politisch-kulturelle Einflüsse unterstützten die Entstehung und Festigung eines bürokratischen Formalismus. In der Übergangszeit erscheint es so, als ob Management neu definiert werde und die Managementkultur sich verändert. Dieser Artikel versucht diese Veräderugen in Kultur und Identität des Rumänischen Managements nachzuvollziehen und an einer Reihe von Organisationen zu überprüfen. Er untersucht zudem, wie stark anglo-amerikanische Werte des Human Recource Management und des Management relevant sind für ein Land dessen historische und kulturelle Erfahrung sich so auffallend deutlich von der des Westens unterscheidet.
Keywords: 650; management; anglo - American model of HRM; leadership